2012 International Conference on Social Informatics 2012
DOI: 10.1109/socialinformatics.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Academic Conferences: Real-Time Visualization and Retrospective Analysis of Backchannel Conversations

Abstract: Abstract-Social-media-supported academic conferences are becoming increasingly global as people anywhere can participate actively through backchannel conversation. It can be challenging for the conference organizers to integrate the use of social media, to take advantage of the connections between backchannel and front stage, and to encourage the participants to be a part of the broader discussion occurring through social media. As academic conferences are different in nature, specialized tools and methods are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Conference organizers have also taken advantage of Twitter by creating conference‐specific hashtags to structure online conversation, which allows for the creation of communities of interest and real‐time conversations during events (Ferguson et al, ; Jalali & Wood, ; Weller et al, ). Use of Twitter for this function has led to the creation of a visualization dashboard created expressly for monitoring academic conference Twitter activity (Sopan et al, ). Conference tweets tend to be directly related to sessions, with a small minority focused on socializing (Chaudhry et al, ; Mishori, Levy, et al, 2014).…”
Section: Social Media Use In Academiamentioning
confidence: 99%
“…Conference organizers have also taken advantage of Twitter by creating conference‐specific hashtags to structure online conversation, which allows for the creation of communities of interest and real‐time conversations during events (Ferguson et al, ; Jalali & Wood, ; Weller et al, ). Use of Twitter for this function has led to the creation of a visualization dashboard created expressly for monitoring academic conference Twitter activity (Sopan et al, ). Conference tweets tend to be directly related to sessions, with a small minority focused on socializing (Chaudhry et al, ; Mishori, Levy, et al, 2014).…”
Section: Social Media Use In Academiamentioning
confidence: 99%
“…McNely [24] suggests that the problem has been partially solved by the increased availability of micropost web services like Twitter, their simplicity of use, and the large adoption rate. Sopan et al [30] showed that a micropost backchannel during a conference, like in our case, permits to connect local and distant participants. In another academic context, Harry et al [23] implemented and described the use of a backchannel to leverage participation in an auditorium to allow for the audience to vote on questions and give feedback.…”
Section: Backchannels For Live-eventsmentioning
confidence: 65%
“…By studying three conferences in 2009 they found that the micro-blogging activity during the conference is not a single conversation but rather multiple monologues with few dialogues between users and that the use of Twitter expands the participation of members of the research community. With respect to applications, Sopan et al [20] created a tool that provides real-time visualization and analysis for backchannel conversations in online conferences.…”
Section: Related Workmentioning
confidence: 99%